First description of Cedicoides pavlovskyi female (Aranei: Trionycha) and comments on taxonomic placement of Cedicus and related genera - Marusik Yuri M; Zonstein Sergei L; Koponen Seppo (KMK SCIENTIFIC PRESS LTD, MOSCOW STATE UNIV, 2025)
Previously unknown female of Cedicoides pavlovskyi (Spassky, 1941), a species restricted to Tajikistan, is described. Three related genera, Cedicus Simon, 1875, Cedicoides Charitonov, 1946 and Paracedicus Fet, 1993, long time ping ponging from family to family, vis. Agelenidae, Cybaeidae, Desidae and Amphinectidae, are briefly discussed and a new subfamily name is proposed for them, Cedicinae subfam.n. The new subfamily is placed into Desidae. How to cite this paper: Marusik Yu.M., Zonstein S.L., Koponen S. 2023. First description of Cedicoides pavlovskyi female (Aranei: Trionycha) and comments on taxonomic placement of Cedicus and related genera // Arthropoda Selecta. Vol.32. No.1. P.98-102. doi: 10.15298/arthsel.32.1.10